Fluorine content of several brands of chocolate bars and chocolate cookies found in Brazil (Pesquisa Odontológica Brasileira, 2003)
Chocolate bars and chocolate cookies are foodstuffs highly appreciated by children. The possibility of having fluorine (F) among their components, associated with an excessive consumption, may make them decisive contributors to the total daily F intake. Thus, they could participate in the establishment of dental fluorosis. The aim of this study was to analyze the fluorine concentration [F] of the chocolates bars (CB) Baton, Confeti, Garoto Ball, Kinder Ovo, M&Ms, Milkybar, Nescau, Nescau Ball, Surpresa, Surpresa Bichos, Tortuguita; and of the chocolate cookies (CC) Danyts, Hipopó, Nescau, Passatempo, Pokémon, Sítio do Pica-Pau Amarelo and Trakinas. Samples were purchased in Bauru, São Paulo, Brazil. Three grams of each product were previously ashed at 525°C (CB and cookies fillings) and at 550°C (cookies dough), during 4 hours. Fluorine was separated from the ash by hexamethyldisiloxane (HMDS)-facilitated diffusion. Fluorine analysis was carried out with the specific electrode. Mean [F]s ± SD and amplitude (unit mg/g) were: CB = 0.30 ± 0.45 (0.07 - 1.60, n = 12) and CC = 1.08 ± 2.64 (0.04 - 7.10, n = 7). It was concluded that some of the analyzed foods may be important contributors to the total daily F intake. As for the product that had the highest [F] (Danyts), when only 3 units are consumed just once a day, they may supply up to 40% of the maximum recommended daily F intake (0.07 mg/kg body weight) for a 2-year-old child (12 kg). The [F] in these products should be informed on their labels.